Penerapan Model Pembelajaran Inkuiri Terbimbing Pada Mata Pelajaran IPS Untuk Meningkatkan Keterampilan Berpikir Kritis Dan Hasil Belajar Siswa Kelas V SD Negeri 1 Poka: Indonesia - Tambunan, Ester Devina; Samuel Patra Ritiauw; , Elsinora Mahananingtyas (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the application of guided inquiry learning model in improving critical thinking skills and learning outcomes of fifth grade students of SD Negeri 1 Poka. This research uses a combination of qualitative and quantitative methods or mix-method. Qualitative data was obtained using interviews while quantitative data was obtained using questionnaires. The research subjects were fifth grade students of SD Negeri 1 Poka, totaling 20 students consisting of 11 male students and 9 female students. The results showed that 1) the guided inquiry learning model can improve students' critical thinking skills and learning outcomes, 2) the application of the guided inquiry learning model can improve students' critical thinking skills and learning outcomes. The effectiveness can be seen in the average value obtained from the final test results (Posttest) which is 86.7% in learning outcomes, while in the level of critical thinking skills with the average value obtained from the final test results (Posttest) which is 59.5% which is quite effective.